The LOGIC of National Policies and Strategies for Open Educational Resources - Mulder, Fred (International Review of Research in Open and Distributed Learning, 2013)
In its first decade (2001-2010) the OER movement has been carried by numerous relevant and successful projects around the globe. These were sometimes large-scale but more often not, and they were primarily initiated by innovating educational institutions and explorative individual experts. What has remained, however, is the quest for a sustainable perspective, in spite of the many attempts in the OER community for clear-cut solutions to the problem of sustainability. This is a major barrier for mainstreaming the OER approach in national educational systems. At the end of the first decade, and more so at the beginning of the second decade (2011-2020), we are witnessing in a few countries emerging efforts to develop and establish a national OER approach. That is required in order to break down the barrier for mainstreaming OER. Making the OER approach sustainable cannot be left to the educational institutions only, but should be facilitated in a national setting.